Chapter Employability and Transitions towards Work: MSc Degree Programme in Educational Planning and Human Resource Development, Catholic University of the Sacred Heart of Brescia - Vischi, Alessandra (Studies on Adult Learning and Education, 2018)
The acceleration of changes underlines the need to enhance our efforts to adapt education to the dynamics of the current economic situation and the issue of employment. In the framework of the circular economy, pedagogy, which is based on the educability of individuals, takes into consideration forms of educational planning to identify a long-lasting balance between economic prosperity, social wellness, and environmental development. The challenge of the future is the possibility of increasing youth employment; this calls for pedagogical expertise and organizational planning to ensure that everyone's development is authentic and holistic. To this end, the MSc Degree programme in Educational Planning and Human Resource Development offered by the Catholic University trains graduates to become professional figures with expertise in coordinating and managing the development of human resources (guidance, selection, personal services); the professional training and retraining of project managers in social and educational contexts for both academic and corporate spheres. The guiding vision behind the MSc in Educational Planning and Human Resource Development is fully in line with the Catholic University of the Sacred Heart's educational project, to support a culture of responsibility and creativity, entrepreneurism and collaboration, multi-disciplinary knowledge and skills, and scientific research for the purpose of holistic human development. Educational planning, in a period of socio-economic and social change, involving the whole planet in many respects, can relaunch an 'integral model of development', based on long-term wellbeing, technological innovation, 'human development', and the dignity of work